OSTERMANN, Ana Cristina; FONTANA, Beatriz. Linguagem, gênero, sexualidade: clássicos traduzidos - Andrade, Daniela Negraes Pinheiro (Revista Estudos Feministas, 2011)
OSTERMANN, Ana Cristina; FONTANA, Beatriz. Linguagem, gênero, sexualidade: clássicos